2017
DOI: 10.3892/etm.2017.4933
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound with a novel nanoparticle contrast agent for clinical diagnosis in patients with non-small cell lung cancer

Abstract: Abstract. Non-small cell lung cancer (NSCLC) initiates in the non-small cells of the lung and is one of the most common types of human cancer. It is known for its rapid growth, easy migration, invasion and reoccurrence, and has the highest incidence rate of all types of cancer. Early detection of NSCLC is difficult to achieve and this is the primary reason for low survival rates in NSCLC. Contrast-enhanced ultrasound is the most common application for evaluating patients diagnosed with NSCLC. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…As the Raman imaging technique develops and its sensitivity increases, it is anticipated that imaging of nanocarrier placement in living systems in real time will be possible in the future. Nanoparticles are used in contrast agents due to their biocompatibility, high X-ray absorption coefficient and the ability to target a specific pathological tissue [63,64]. In addition, the nanoparticle contrast agent administered during the study improves the quality and resolution of the image, which allows earlier detection of lesions in the body.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…As the Raman imaging technique develops and its sensitivity increases, it is anticipated that imaging of nanocarrier placement in living systems in real time will be possible in the future. Nanoparticles are used in contrast agents due to their biocompatibility, high X-ray absorption coefficient and the ability to target a specific pathological tissue [63,64]. In addition, the nanoparticle contrast agent administered during the study improves the quality and resolution of the image, which allows earlier detection of lesions in the body.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…It has been reported that developing multimodal contrast agent would enhance the diagnostic accuracy of PET/CT, as well as increase the diagnostic accuracy sensitivity in patients with lung cancer (23). A previous study reported that contrast-enhanced ultrasound with a novel nanoparticle contrast agent increases the diagnostic efficacy in patients with NSCLC (24). In addition, another study reported a composite nano-system composed of gadolinium-doped mesoporous silica nanoparticles and gold nanoparticles, which can be used as an efficient contrast agent for in vivo cancer imaging (25).…”
Section: Role Of Gd 2 O 3 -Doped Carbon-11-choline-lenvatinib Nanoparmentioning
confidence: 99%
“…both imaging and therapeutic purposes. Li et al [11] used multi-targeted tyrosine kinase inhibitor Lenvatinib which covalently bound with the superparamagnetic iron oxide nanoparticles (SPIONs) to improve US image quality. They have reported that contrast-enhanced ultrasound improved the imaging quality and diagnostic accuracy of an early stage of non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%